Evaluating Forestry Holding of Cendana Library’s Collection Using Conspectus - Handisa, Rattah Pinnusa (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2019)
Background of the study: Evaluating collection is required by libraries to assess the strengths and the weaknesses of collections. This research gives a benefit for libraries to improve their collection development policies. Thus, the libraries can provide adequate numbers of collections to meet the patrons? demands.Purpose: The purpose of this report is to evaluate the forestry holdings in the Cendana library of Forest Research Institute Kupang (FRIK) by using conspectus.Method: This research is an explanatory study cases in order to describe strength and weakness of forestry holding at Cendana library. The evaluator uses the Australian conspectus due to relevancy. The conspectus has several techniques for collecting data. A checklist is used by evaluator to evaluate monographs and electronic books. In addition, the evaluator evaluates the existing collection strengths (ECS), chronological coverages, languages, and physical conditions. The evaluator records these components into the evaluative worksheet.Findings: The result reveals that the forestry holdings in Cendana Library of Forest Research Institute Kupang (FRIK) has conspectus levels in 1b. Although type of the languages become a strength, but the quantity is a weakness. The data shows that the size level of forestry holdings in the Cendana Library of Forest Research Institute Kupang (FRIK) is in the level 1 b.Conclusion: In conclusion, the collection weakness is in books? quantities. The limited number of forestry books enforces the conspectus levels of forestry holdings in a low level (1b). Meanwhile, strengths of existing collection are the equal portions between foreign language in English and Bahasa and the physical condition of books. It is recommended that Cendana' library should increase the numbers of collections through procurement or book?s exchange program.